Recent insights into the biology of Barrett's esophagus. Issue 1 (17th July 2020) - Badgery, Henry; Chong, Lynn; Iich, Elhadi; Huang, Qin; Georgy, Smitha Rose; Wang, David H.; Read, Matthew
Abstract: Barrett's esophagus (BE) is the only known precursor to esophageal adenocarcinoma (EAC), an aggressive cancer with a poor prognosis. Our understanding of the pathogenesis and Barrett's metaplasia is incomplete, and this has limited the development of new therapeutic targets and agents, risk stratification ability, and management strategies. This review outlines current insights into the biology of BE and addresses controversies surrounding cell of origin, cellular reprogramming theories, updates on esophageal epithelial barrier function, and the significance of goblet cell metaplasia and its association with malignant change. Further research into the basic biology of BE is vital as it will underpin novel therapies and improve our ability to predict malignant progression and help identify the minority of patients who will develop EAC.